Advocacy workshop training of trainers for Henti.Elak.Basmi.Asap.Tembakau (HEBAT) programme: a UM/UiTM collaboration - Kanoo, Lina Lohshini; Miptah, Hayatul Najaa; Nik Mohd Nasir, Nik Munirah; Ismail, Ilham Ameera; Abd Razak, Suraya (Faculty of Medicine, 2024)
20TH JANUARY 2024 - It was on a Saturday morning, still fresh into the new year that the Quit Smoking and Adolescent teams from the Department of Primary Care Medicine, Faculty of Medicine, UiTM received a friendly collaborative visit from the researchers under the Nicotine Addiction Research and Collaborating Group (NARCC) Faculty of Medicine, University Malaya.